Casting copper-base alloys. (American Foundrymen's Society, 2016)
The original contributors to the second edition of the book felt that it was time to update several key chapters and also add a new chapter (Copper Alloys for Special Applications) that deals with the issues that impact the copper industry in the future, specifically copper's antimicrobial properties. Other changes include: updates to conforming specifications; revisions in casting processes and materials; a section on venting added to the Gating chapter; updates to chapters on Leaded and Unleaded Red Brasses, Properties of Cast Copper-Base Alloys and Health & Safety Aspects. The Third Edition contains over 300 pages, with new and updated artwork.
Keywords: Copper founding.; Copper castings.; elektronické knihy; electronic books